A new compact neutron spectrometer - Comrie, Angus (Department of Physics, 2022)
A new compact neutron spectrometer has been designed, developed and characterized. The detector is based on EJ299-33 plastic scintillator coupled to silicon photomultipliers, and a digital implementation of pulse shape discrimination is used to separate events associated with neutrons from those associated with gamma-rays. The spectrometer is suitable over the neutron energy range 1 – 100 MeV, and the development illustrated with measurements made using an Am-Be radioisotopic source, a D-T sealed tube neutron generator and quasi-monoenergetic neutron beams produced using the iThemba LABS cyclotron. A segmented variation of the spectrometer is capable of providing directional information through the comparison of count rates between scintillator cells.